Bercerita Adaptif sebagai Media Komunikasi bagi Anak Autis di TK Tunas Bhakti Semarang - Budiawan, Raden Yusuf Sidiq; Hidayah, Siti Khofifatul; Faiza, Milla Hanifah Ratu; Shobah, Dina Amalia (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Children with Autism Spectrum Disorder (ASD) often experience significant barriers in social interaction and verbal communication. This community service program aimed to explore the effectiveness of adaptive storytelling as a communication medium for children with ASD at TK Tunas Bhakti. The program engaged three children aged 6–7 years through four storytelling sessions using varied media, including real fruits, animated videos, and hand puppets. Activities were designed based on each child’s special interests and emotional readiness, emphasizing narrative participation and expression. Data were collected through observation, interviews, and documentation before and after the sessions. The results showed a marked improvement across multiple indicators: the frequency of initiating speech increased from rare (0–1 times/week) to daily occurrences; responses became more relevant and timely; and story recall shifted from fragmented to sequential and detailed. Children demonstrated greater enthusiasm, expressive intonation, and peer engagement, indicating improved confidence and social interaction. The adaptive nature of the storytelling—tailored to sensory and emotional needs—significantly enhanced communicative effectiveness. The approach not only supported language development but also fostered empathy and emotional connection. This study highlights the potential of adaptive storytelling as both an educational and psychosocial intervention strategy in inclusive early childhood education. Future implementations are encouraged to involve larger participant groups and longer intervention periods to broaden impact.